The morality of drone warfare and the politics of regulation - Schulzke, Marcus (New Security Challenges, 2017)
The book discusses the moral and legal issues relating to military drones, focusing on how these machines should be judged according to the principles of just war theory. It not only considers existing drones like the Predator and Reaper but also evaluates the many types of drones in development.